Co-localization of Nkx6.2 and Nkx2.2 Homeodomain Proteins in Differentiated Myelinating Oligodendrocytes - Cai, Jun (2010)
Recent studies have suggested that Nkx6.2/Gtx and Nkx2.2 homeodomain transcription factors are involved in the regulation of oligodendrocyte maturation and/or myelination which occur predominantly in postnatal stages. However, their cellular specificity in postnatal central nervous system has not been characterized and their dynamic expressional relationship during oligodendrocyte lineage progression has not been determined. Here we report that both Nkx2.2 and Nkx6.2 are selectively expressed in Olig2+ cells of oligodendrocyte lineage in postnatal spinal cords. While Nkx6.2 is specifically expressed in the APC+ mature oligodendrocytes, Nkx2.2 is initially expressed in differentiating oligodendrocyte precursor cells (OPCs) but quickly down-regulated as OPCs undergo terminal differentiation. Intriguingly, Nkx2.2 expression is up-regulated in mature myelinating oligodendrocytes at later stages. The co-expression of Nkx2.2 and Nkx6.2 transcription factors in myelinating oligodendrocytes suggests their functional interactions in the regulation of myelin sheath formation and/or maintenance.